Malva neglecta essential oil: A promising approach for bio-preserving mayonnaise and assessing variable correlations through principal component analysis and heat map - Amin Abbasi; Hedayat Hosseini; Hadi Pourjafar; Samaneh Moradi; Saeedeh Shojaee-Aliabadi (Heliyon)
Consumers increasingly regard plant-derived biocompounds as a safe alternative to synthetic additives. To increase shelf life and enhance safety status, this study sought to determine how Malva neglecta essential oil (MNEO) might affect microbiological and chemical changes in mayonnaise samples at 4 °C. MNEO was extracted, and the primary chemical constituents were identified using a GC-MS. Based on the determined MIC/MBC, various concentrations of MNEO have been utilized in the preparation of mayonnaise and evaluated for microbial, chemical, and sensorial characteristics for 40 days at 4 °C. MNEO contains podocarpa-8,11,13-trien-3-one, 12-hydroxy-13-isopropyl, δ-elemene, γ-elemene, bicyclogermacrene, β-ylangene, viridiflorol, spathulenol, 6,10,14-trimethyl-2-pentadecanone, L-linalool, γ-curcumene, germacrene D, n-tetradecane, β-elemene, β-damascenone, δ-cadinene, α-muurolol, cis-muurola-3,5-diene, and α-cadinol with substantial antibacterial and antioxidant properties. The MNEO-based bio-preservation strategy efficiently diminished microbial growth (S. aureus > E. coli O157:H7 > P. aeruginosa > S. enteritidis) and augmented the mayonnaise sample's shelf life (>40 days). When MNEO was utilized at 5084 ppm, the oxidative stability of the specimens was also more effectively preserved at optimal levels (peroxide values of 1.76, 1.98, and 2.34 meq O2/kg of oil for TBHQ, 5084 ppm, and 2542 ppm treatments, respectively) (P < 0.05). Furthermore, it was noted that the specimens exposed to 5084 ppm MNEO had the highest sensory evaluation scores regarding aroma, hue, flavor, consistency, and general appeal (P < 0.05). Using MNEO at the recommended concentration (5084 ppm) significantly reduces microbiological and chemical deterioration in mayonnaise throughout preservation (greater than 40 days) without causing any adverse sensory consequences.